Security improvement of power systems by using trajectory sensitivity approaches - Zamora Cárdenas, Enrique Arnoldo (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
The security assessment of power systems represents one of the principal studies that must be carried out in energy control centers. The major computational burden on security assessment is spent in the security evaluation of the critical contingencies. In this research several approaches are proposed to improve the dynamic security of power systems. These approaches are based on quantifying the parameters influence on the angular stability of the power systems via the trajectory sensitivities obtained with respect to the system parameters. In order to implement these approaches a digital program of transient stability was developed in language C++ by following an Object Oriented Programming philosophy (OOP). The power system is represented by means of Differential-Algebraic Equation (DAE) systems, and the angular stability model is based on the power balance formulation. The transient stability solution uses the Simultaneous Implicit method (SI) of integration, which consists of implicitly integrating the differential equations, so that the resulting algebraized set of equations is solved together with the existent algebraic set of equations under a unified frame of reference. Furthermore, sparsity and pre-ordering techniques were considered in order to achieve a very important reduction in the computational burden. The efficient assessment of the parameter influence is accomplished by implementing the Staggered Direct Method (SDM), which consists of the analytical computation of the linear Trajectory Sensitivities (TS) at each time step of integration. The solution then requires only one forward/backward substitution at each integration step. This method is straightforwardly extended in order to compute a sensitivity function matrix obtained with respect to multiple system parameters at the same simulation.

La evaluación de la seguridad de los sistemas eléctricos representa uno de los principales estudios que deben realizarse en los centros de control de energía. La mayor carga computacional sobre la evaluación de seguridad se gasta en la evaluación de la seguridad de las contingencias críticas. En esta investigación se proponen varios enfoques para mejorar la seguridad dinámica de los sistemas de energía. Estos enfoques se basan en la cuantificación de los parámetros de influencia sobre la estabilidad angular de los sistemas de potencia a través de las sensibilidades de la trayectoria obtenida con respecto a los parámetros del sistema. Para implementar estos enfoques se desarrolló un programa digital de estabilidad transitoria en lenguaje C ++ siguiendo una filosofía de programación orientada a objetos (OOP). El sistema de potencia se representa mediante sistemas de Ecuación Diferencial-Algebraica (DAE), y el modelo de estabilidad angular se basa en la formulación del equilibrio de potencia. La solución de estabilidad transitoria utiliza el método implícito simultáneo (SI) de integración, que consiste en integrar implícitamente las ecuaciones diferenciales, de manera que el conjunto algebraizado resultante de ecuaciones se resuelve junto con el conjunto algebraico existente de ecuaciones bajo un marco unificado de referencia. Además, se consideraron técnicas de escasez y pre ordenamiento para lograr una reducción muy importante en la carga computacional. La evaluación eficiente de la influencia del parámetro se logra mediante la implementación del Método Directo Escalonado (SDM), que consiste en el cálculo analítico de las Sensibilidades de Trayectoria lineal (TS) en cada paso de tiempo de integración. La solución entonces requiere solamente una sustitución hacia delante / hacia atrás en cada paso de integración. Este método se extiende directamente para calcular una matriz de función de sensibilidad obtenida con respecto a múltiples parámetros del sistema en la misma simulación.
Facultad de Ingeniería Eléctrica. Doctorado en Ciencias en Ingeniería Eléctrica
Keywords: info:eu-repo/classification/cti/7; FIE-D-2010-0017; Seguridad; Energía; Sistemas